2005
DOI: 10.1002/hbm.20125
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity associated with painfully hot stimuli applied to the upper limb: A meta‐analysis

Abstract: Abstract:The capacity of pain to alert against potential injury or focus attention on damaged tissue is enhanced by the intrinsically aversive nature of the experience. Finding methods to relieve pain will ultimately be facilitated by deeper understanding of the processes that contribute to the experience, and functional brain imaging has contributed substantially toward that end. An impressive body of literature has identified a distributed network of pain-related activity in the brain that is subject to cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
78
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 62 publications
11
78
0
Order By: Relevance
“…We also found activation in the anterior insular cortex, and this too is known to be activated during anticipation of pain, experience of pain, and empathy for pain (15)(16)(17). Coactivation of the ACC and anterior insula in imaging experiments is strongly linked to emotional processing and introceptive awareness (28,35,36). The activity in these areas probably reflected anxiety because there was a correlation between the increase in anxiety in the ownership condition and the increase in the threat-evoked BOLD responses in the ACC and insular cortex in this condition (SI Fig.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…We also found activation in the anterior insular cortex, and this too is known to be activated during anticipation of pain, experience of pain, and empathy for pain (15)(16)(17). Coactivation of the ACC and anterior insula in imaging experiments is strongly linked to emotional processing and introceptive awareness (28,35,36). The activity in these areas probably reflected anxiety because there was a correlation between the increase in anxiety in the ownership condition and the increase in the threat-evoked BOLD responses in the ACC and insular cortex in this condition (SI Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, activity in the SMA and pre-SMA increases before voluntary movement, reflecting the preparation to move (21)(22)(23)(24)(25). It is also commonly observed that medial wall motor areas are activated when humans experience or anticipate painful stimuli (16,(26)(27)(28). It has been suggested that this motor activity reflects the urge to remove the hand (27,29) or preparation to generate an escape motor response (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of thirst-related brain activity have identified a network including the hypothalamus, thalamus, insula, parahippocampus, somatosensory cortex, anterior cingulate, posterior cingulate, and cerebellum (1,(10)(11)(12). A metaanalysis of pain imaging studies revealed a consistent network incorporating activity in the diencephalon and posterior parietal, insula, and limbic cortices and cerebellum (13). Craig (2) and Vogt (14) have suggested that the insula and anterior cingulate are key loci in the conscious experiences arising from interoceptive inputs.…”
mentioning
confidence: 99%